PENGARUH KOMITE AUDIT DAN KUALITAS AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PADA TAHUN 2017 – 2021 - Hardika Nugroho Saputra; Sasmita Sari Ardaninggar (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of company audit committees and auditor quality on audit delay. The independent variables used in this study are the audit committee and auditor quality. As for the dependent variable in this study is audit delay. The sample selection in this study used a purposive sampling method. The samples selected in this study are 15 property and real estate companies listed on the IDX for the 2017-2021 period. The results of the study show that simultaneously the two independent variables have a significant influence on audit delay. Partially, the audit committee has a significant negative effect on audit delay, while the auditor quality variable has no effect on audit delay.